Polipropileno modificado com semicondutores a base de prata: compósitos com alta potencialidade contra SARS-CoV-2 e outros patógenos - Ribeiro, Lara Kelly (2023)
The worldwide outbreak of the coronavirus (COVID-19) pandemic and other emerging infections is difficult and sometimes impossible to treat, making them one of the major public health issues of recent times. It is noteworthy that Ag based semiconductors can help to orchestrate several strategies to combat this serious social problem. In this thesis, we present the synthesis of Ag3PO4, α Ag2WO4, β-Ag2MoO4 and Ag2CrO4 and their immobilization in polypropylene in amounts of 0.5, 1.0 and 3.0% (w/w), respectively. Synthesized materials were characterized by XRD, Raman spectroscopy, FTIR spectroscopy, AFM, UV-vis spectroscopy, rheology, SEM and contact angle to confirm their structural integrity. The activity of the composites was investigated against the Gram negative bacteria Escherichia coli, the Gram-positive bacteria Staphylococcus aureus and the fungus Candida albicans. The best antimicrobial efficiency was obtained by the composite with α-Ag2WO4, which completely eliminated microorganisms within 4 h of exposure. The composites were also tested for inhibition of the SARS-CoV-2 virus, showing antiviral efficiency greater than 98% in just 10 min. Furthermore, based on the results of first principles calculations at the density functional level, a plausible reaction mechanism for the initial events associated with the generation of both hydroxyl radicals •OH and superoxide radical anion •O2– on the more reactive surface (110) of the Ag3PO4 semiconductor. The stability of the antimicrobial activity was evaluated, resulting in constant inhibition, even after the aging of the material. The antimicrobial activity of the compounds was attributed to the production of reactive oxygen species by semiconductors, which can induce high local oxidative stress, causing the death of these microorganisms. Ag/PP-based semiconductor composites have proven to be an attractive outlet for providing humans with a broad spectrum of biocidal activity.